Evaluating the Mechanical Properties of Tensile Strength and Hardness after Optimization during a Mild Steel Metal Plate Welding Operation - S. O. Emumena; A. Akpotor; S. O. Sada; J. Sinebe (Journal of Applied Sciences and Environmental Management)
The choice of choosing between alternatives is a prerequisite for a chain of different engineering selection problems, such as process selection, machine selection, tools selection, material handling equipment selection, supplier selection. Hence, the objective of this paper was to evaluate the mechanical properties of tensile strength and hardness after optimization using the application of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) during a steel metal welding process. The result obtained reveals that the weld current 170amp, weld voltage 20v, filler rod diameter 22mm and gas flow rate 3.3lit/min gave the optimal tensile strength of 496.5N/mm2 and Hardness of 190.2.